2014
DOI: 10.1111/jne.12188
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Mood Adaptations in the Peripartum Female: Complementary Contributions of GABA and Oxytocin

Abstract: Peripartum hormones and sensory cues from young modify the maternal brain in ways that can render females either at risk for, or resilient to, elevated anxiety and depression. The neurochemical systems underlying these aspects of maternal emotional and mood states include the inhibitory neurotransmitter GABA and the neuropeptide oxytocin (OXT). Data from laboratory rodents indicate that increased activity at the GABAA receptor contributes to the postpartum suppression of anxiety-related behaviour that is media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 226 publications
5
68
0
4
Order By: Relevance
“…The observed epigenetic changes we report here are in line with the predictive adaptive response model (Gluckman et al, 2005): If reduced levels in OXTR methylation relate to increased expression levels (Kusui et al, 2001) and elevated OXTR abundance, we speculate that this epigenetic adaptation might compensate some of the effects of maternal adversities during pregnancy and postpartum. While several studies indicated that oxytocin receptor expression and OXTR binding is elevated in several brain areas during parturition and breastfeeding and linked to reduced anxiety and depression in the mother (Lonstein et al, 2014), oxytocin signaling in offspring is less well studied. Intriguingly, rodent studies suggest that exposure to prenatal and postnatal maternal stress decreased the number of oxytocin positive cells in adult offspring as compared with offspring from non-stress exposed mothers (de Souza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed epigenetic changes we report here are in line with the predictive adaptive response model (Gluckman et al, 2005): If reduced levels in OXTR methylation relate to increased expression levels (Kusui et al, 2001) and elevated OXTR abundance, we speculate that this epigenetic adaptation might compensate some of the effects of maternal adversities during pregnancy and postpartum. While several studies indicated that oxytocin receptor expression and OXTR binding is elevated in several brain areas during parturition and breastfeeding and linked to reduced anxiety and depression in the mother (Lonstein et al, 2014), oxytocin signaling in offspring is less well studied. Intriguingly, rodent studies suggest that exposure to prenatal and postnatal maternal stress decreased the number of oxytocin positive cells in adult offspring as compared with offspring from non-stress exposed mothers (de Souza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One candidate gene is the oxytocin receptor gene (OXTR), which is expressed in several brain regions implicated in social behavior and bonding, as well as in various peripheral tissues (Kimura et al, 2003). The oxytocinergic system is implicated in reproductive behavior, such as induction of labor and lactation, and has important function in mother-child bonding and maternal psychological wellbeing, including depression and anxiety (Lonstein et al, 2014). Fluctuations in maternal oxytocin levels from early to mid pregnancy and the early postpartum show great variety between individuals, ranging from stable to increased or even decreased oxytocin levels during the course of pregnancy .…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that PPD may result from: (a) inability of the hypothalamic–pituitary–adrenal (HPA) axis to maintain homeostasis when exposed to challenges like pregnancy and parturition (Jolley, Elmore, Barnard, & Carr, 2007); (b) postpartum hormonal withdrawal from high prenatal levels of progesterone and estrogen (Corwin & Pajer, 2008; Deecher et al., 2008); and (c) immune activation associated with pregnancy and parturition (Maes, Ombelet, Verkerk, Bosmans, & Scharpe, 2001; Maes et al., 2002). Even less is known about the biological etiology of PPA, but research has identified some significant biological correlates of PPA that overlap with PPD, including levels of estrogen, progesterone, adrenal corticosteroids, prolactin, oxytocin, norepinephrine, and serotonin (Lonstein, Maguire, Meinlschmidt, & Neumann, 2014). These diverse findings suggest additional biobehavioral contributors to PPD/A yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the work in this realm is sometimes equivocal and often has not examined individual differences in naturally occurring ovarian steroid levels, their change across long periods of time, or individual differences in females' responses to exogenous steroids that would best speak to our focus here on factors underlying susceptibility or resilience. We also will not discuss in detail the neurobiological systems involved in postpartum anxiety and depression, as numerous thorough recent reviews have been devoted to this goal (Gobinath et al, 2014;Krishnan and Nestler, 2008;Lonstein, 2007;Lonstein et al, 2014;Macbeth and Luine, 2010;Nestler et al, 2002). We hope that examining some of the often ignored non-hormonal factors affecting anxiety and depressive responses in human and rodents mothers will broaden the perspective on this topic, inform us about cross-species conservation of the determinants underlying postpartum affective states, and ultimately help alleviate the negative consequences of anxiety and depressive disorders on affected women and their children.…”
Section: Accepted Manuscriptmentioning
confidence: 99%